The Barocene Era - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
This communication defines and describes the Barocene era, as that phase of human development which is characterized by a major impact of overweight and obesity. We use this term to highlight the fact that overweight and obesity need to be prevented and managed on an urgent footing. If not checked, these endocrine diseases will retard our growth and reduce our well being Keywords: Health economics, health policy, obesity, overweight, psychosocial aspects.